Effects of mixed reality head-mounted glasses during 90 minutes of mental and manual tasks on cognitive and physiological functions - Cometti, Carole; Païzis, Christos; Casteleira, Audrey; Pons, Guillaume; Babault, Nicolas (PeerJ (San Francisco, CA), 2018)
We evaluated the effects of a mixed reality (MR) head-mounted deviceon some cognitiveand physiological functions during 90 min tasks in an attempt to determine their safety for workers. A total of 12 volunteers performed 90-min intellectual and manual tasks with and without MR glasses. Balance, Stroop, and memory tests were conducted before, during and after these tasks. Heart rate and electromyographic activity of some muscles were recorded. A survey was used to determine subjective fatigue, pain, or discomfort. Balance, heart rate, rate of perceived exertion, memory, and attention were unaffected by wearing MR glasses. Electromyographic activity increased with MR glasses for deltoid, biceps brachii, and soleus muscles. Few subjects reported discomfort, pain, or visual fatigue with MR glasses. Some participants reported they lost the notion of time and reality. Accordingly, we concluded that the MR glasses under investigation (Hololens) can be used safely. An appropriate setup and familiarization are needed to optimize use.